2008
DOI: 10.1117/1.3041492
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of zinc oxide nanoparticle penetration in human skin in vitro and in vivo

Abstract: Abstract. Zinc oxide ͑ZnO-nano͒ and titanium dioxide nanoparticles ͑20 to 30 nm͒ are widely used in several topical skin care products, such as sunscreens. However, relatively few studies have addressed the subdermal absorption of these nanoparticles in vivo. We report on investigation of the distribution of topically applied ZnO in excised and in vivo human skin, using multiphoton microscopy ͑MPM͒ imaging with a combination of scanning electron microscopy ͑SEM͒ and an energy-dispersive x-ray ͑EDX͒ technique t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
171
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 276 publications
(183 citation statements)
references
References 30 publications
10
171
1
1
Order By: Relevance
“…Permeability of each sized NP made no difference in excised human skin, and no "viable" epidermal penetration was observed. The results were consistent with some reports using human skin 8,18,21 and animal skin. 16,17 Barrier function of SC against molecule penetration in general depends on its protein, lipid and water compartments.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…Permeability of each sized NP made no difference in excised human skin, and no "viable" epidermal penetration was observed. The results were consistent with some reports using human skin 8,18,21 and animal skin. 16,17 Barrier function of SC against molecule penetration in general depends on its protein, lipid and water compartments.…”
supporting
confidence: 83%
“…8 Zvyagin et al 18 suggested that animal skin represents a poor model for human skin for the studies on NP transdermal penetrability. Differences between these skins, especially hair follicle density, SC thickness, whole skin and skin lipid mass, 19 could lead to different results.…”
mentioning
confidence: 99%
“…In humans, environmental exposure to nano-ZnO has shown that it stayed in the stratum corneum and accumulated in skin folds and/or hair follicle roots of the skin. 5 Also, exposure to low concentrations of nano-ZnO indicates a genotoxic potential mediated by lipid peroxidation and oxidative stress in epidermal cells. …”
Section: Introductionmentioning
confidence: 99%
“…The main drawback of tagging with traceable molecules is potential detachment from the nanoparticles via spontaneous or enzyme-catalyzed reactions in vivo. [17][18][19][20] The dissociation of Cy5.5 from nanoscaled ZnO nanoparticles after 3 hours is inconsequential because the gastric emptying rate is faster than the time needed to dissociate Cy5.5.…”
Section: Discussionmentioning
confidence: 99%